Pengembangan Media Puzzle Raja untuk Keterampilan Menulis Aksara Jawa Siswa Sekolah Dasar - Vikaharista Ayuningtyas; Filia Prima Artharina; Suyitno Suyitno (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to develop learning media for Javanese script puzzles in Javanese language learning, on Javanese script writing material at the elementary school level and to improve Javanese script writing skills for students as well as analyze the feasibility and practicality of learning media. This type of research is Research and Development (R&D). The development method by Borg and Gall uses 8 steps, namely research and initial information gathering, planning, product format development, trials, revisions, field trials, field trial revisions. The subjects in this study were fourth grade students at SDN Tombo 01, Bandar District, Batang Regency. Data collection techniques in the form of interviews, observation, questionnaires, and documentation. Data were analyzed qualitatively from the results of interviews with class IV teachers at SDN Tombo 01, as well as quantitative analysis from the results of media expert questionnaires, material expert questionnaires, class teacher response questionnaires, and student response questionnaires. The results of the study entitled "Development ofÂ  Puzzle Raja Media for Javanese Script Writing Skills for Elementary School Students" concluded that the learning media complies with the Borg and Gall development procedure to obtain feasible and practical criteria applied to Javanese language learning in Javanese script material, elementary school.